MIĘDZY TRADYCJĄ A NOWOCZESNOŚCIĄ (?) O DWÓCH TŁUMACZ(ENI)ACH OŻENKU NIKOŁAJA GOGOLA - Lubocha-Kruglik, Jolanta Krystyna (Przegląd Rusycystyczny, 2017)
Jolanta Lubocha-Kruglik BETWEEN TRADITION AND MODERNITY (?) ON TWO TRANSLATIONS AND TRANSLATORS OF MARRIAGE BY N. GOGOL Summary The article is devoted to two Polish translations of Marriage one of the best-known plays by Nikolai Gogol. Polish readers and audience have known the play owing to the translation (1937) of an outstanding poet Julian Tuwim. In his times this translation was considered to be very innovative. It can be seen as strong opposition not only to the translation tradition but also to the reader’s habits. In 2015 a new translation was ordered by the theatre and made by Agnieszka Lubomira Piotrowska — one of the best-known translators of Russian literature in Poland. As she claims her text was not updated, but she translated it in accordance with the rhythm and pace of the contemporary Polish language trying to preserve Gogol’s style.